THE LEAN MANAGEMENT OF SPORTS AND SCHOOL ACTIVITY DIRECTORS AND ITS RELATION TO THE ADMINISTRATIVE EFFICIENCY OF TECHNICAL SUPERVISORS IN BAGHDAD'S EDUCATION DIRECTORATES - Diyar Kareem Najm; Diyar Fakhrulddin Mohammed; Ola Sabri Hazim (Sports Collaboration Journal, 2025)
Lean management has gained recognition in recent years as a practical approach in several public and educational organizations to reduce expenses, improve resource utilization, and increase service quality. In contrast, empirical information on its implementation in sports and school activity administration in developing educational systems and its connection to the administrative efficiency of technical supervisors is somewhat limited. The study sought to understand the role of lean management in the administrative efficiency of technical supervisors in school and sports activities in the directorates of education in Baghdad, including the development of an empirical study with the following: 1. Developing a measuring instrument for lean management dimensions and developing a measuring instrument for administrative efficiency 2. Validate the measuring instrument of lean management dimensions in administrative efficiency 3. Measure the extent of the impact of the lean management on the efficiency of the supervisors in the administration of sports and school activities in the directorates of education in Baghdad. The study employed a descriptive correlational design. The study population included all 208 technical supervisors in the Baghdad Education Directorates, encompassing Karkh 1, Karkh 2, Karkh 3, Rusafa 1, Rusafa 2, and Rusafa 3 directorates, and a census approach was applied. Two questionnaires were developed and utilized, namely, the Lean Management Questionnaire and the Administrative Efficiency Questionnaire. The collected data were subjected to statistical analyses using SPSS software to examine the relationships between variables. The validity, reliability, and strength of the correlation between variables were calculated using the survey sample. Results of the study indicated a positive, strong, and direct relationship between lean management and administrative efficiency among the technical supervisors of the directorates of education. Furthermore, lean dimensions, including teamwork cohesion, flexibility in decision-making, continuous improvement, and several others, showed a strong relationship with productivity, improved coordination, and effective administrative performance. The study concludes that the effective implementation of lean management can lead to administrative efficiency among technical supervisors in school and sports activities, thus confirming the study hypotheses. Continuous professional training, promoting a collaborative work culture, and developing decision-making competencies will be critical for reaping the maximum benefits of lean management in the educational directorates.